Tree hole mosquito species composition and relative abundances differ between urban and adjacent forest habitats in northwestern Argentina - Mangudo, Carolina (2017)
Water holding tree holes are main larval habitats for many pathogen vectors, especially mosquitoes (Diptera: Culicidae). Along three years, the diversity and composition of mosquito species in tree holes of two neighbouring but completely different environments, a city and its adjacent forest, were compared using generalized linear mixed models, PERMANOVA, SIMPER and species association indexes. The city area (Northwest Argentina) is highly relevant epidemiologically due to the presence of Aedes aegypti L. (main dengue vector) and occurrence of dengue outbreaks; the Yungas rainforests are highly biologically diverse. In total 7 mosquito species were recorded, in descending order of abundance: Ae. aegypti, Haemagogus spegazzinii Brèthes, Sabethes purpureus (Theobald), Toxorhynchites guadaloupensis Dyar and Knab, Aedes terrens Walker, Haemagogus leucocelaenus Dyar & Shannon and Sabethes petrocchiae (Shannon and Del Ponte). The 7 mosquito species were recorded in both city sites and forested areas; however, their mosquito communities significantly diverged because of marked differences in the frequency and relative abundance of some species: Tx. guadeloupensis and Ae. aegypti were significantly more abundant in forest and urban areas, respectively. Positive significant associations were detected between Ae. aegypti, Hg. spegazzini and Hg. leucocelaenus. The combined presence of Ae. aegypti, Haemagogus and Sabethes in the area also highlight a potential risk of yellow fever epidemics. Overall results show an impoverished tree hole mosquito fauna in urban environments, reflecting negative effects of urbanization on mosquito diversity.